Major Trends in 21st Century Hindi Novels: A Critical Study: 21वीं सदी के हिंदी उपन्यासों की प्रमुख प्रवृत्तियाँ: एक समीक्षात्मक अध्ययन - Yadav, Hari Kishore; Tiwari, Braj Bhushan (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Contemporary Hindi novels serve as a mirror of the changing landscape of Indian society, politics, and culture. In the twenty-first century, Hindi novels, along with a realist perspective, have brought new discourses—women’s discourse, Dalit discourse, and Adivasi (tribal) discourse—to the forefront, giving literature a multidimensional character. These novels reflect concerns such as women’s identity, caste inequality, social justice, tribal life, displacement, globalization, consumerism, and postmodernism. From the perspective of narrative technique and language, contemporary novels are also moving towards experimentation, where autobiographical elements, reinterpretations of history and memory, and multilayered structures prominently emerge. This research paper presents a critical analysis of the major trends in contemporary Hindi novels. It studies the framework of novels in the context of social realism, women’s perspectives, Dalit consciousness, tribal resistance, historical awareness, postmodernism, and the challenges of globalization. Abstract in Hindi Language: समकालीन हिंदी उपन्यास भारतीय समाज, राजनीति और संस्कृति के बदलते परिदृश्य का दर्पण है। इक्कीसवीं सदी में हिंदी उपन्यासों ने यथार्थवादी दृष्टि के साथ-साथ नए विमर्शों—स्त्री-विमर्श, दलित-विमर्श और आदिवासी-विमर्श—को केंद्र में लाकर साहित्य को बहुआयामी स्वरूप प्रदान किया है। इन उपन्यासों में स्त्री अस्मिता, जातीय असमानता, सामाजिक न्याय, आदिवासी जीवन, विस्थापन, भूमंडलीकरण, बाज़ारवाद और उत्तर-आधुनिकता जैसे सरोकार स्पष्ट दिखाई देते हैं। कथा-शिल्प और भाषा की दृष्टि से भी समकालीन उपन्यास प्रयोगधर्मिता की ओर अग्रसर हैं, जहाँ आत्मकथात्मकता, इतिहास और स्मृति के पुनर्पाठ तथा बहुस्तरीय संरचना प्रमुख रूप से उभरती है। यह शोध-पत्र समकालीन हिंदी उपन्यासों की प्रमुख प्रवृत्तियों का समीक्षात्मक विश्लेषण प्रस्तुत करता है। इसमें सामाजिक यथार्थ, स्त्री-दृष्टि, दलित चेतना, आदिवासी प्रतिरोध, इतिहासबोध, उत्तर-आधुनिकता और वैश्वीकरण की चुनौतियों के अंतर्गत उपन्यासों की रूपरेखा का अध्ययन किया गया है। Keywords: समकालीन हिंदी उपन्यास, प्रवृत्तियाँ, स्त्री-विमर्श, दलित-विमर्श, आदिवासी विमर्श